Pensions and the Challenges of Adequacy and Sustainability: Irish Citizens' Voices and Policy Implications - Emer Mulligan (Intereconomics, 2019)
Population ageing has been identified as a major societal challenge for all Western nations, driven by increasing life expectancies and reduced fertility, and occurring at different paces in countries across the EU and OECD.
Keywords: 330